KEBIJAKAN PENGELOLAAN WILAYAH PERTAHANAN DALAM KONSEP PERTAHANAN PULAU-PULAU BESAR (Studi TNI-AL) - Ruslan Arief; Joni Widjayanto; Priyanto Priyanto (Sekolah Tinggi Pariwisata Mataram, 2021)
The dynamic strategic environment, both global and regional, can have both positive and negative impacts and directly or indirectly affect the development of the national environment. The change in Strategic Environment Development (Banglingstra) will change how a country's strategy is to achieve its national goals. The President of the Republic of Indonesia has signed the General Policy on National Defense, signing PP N0 8 2021 as an elaboration of the Vision and Mission of the elected President in the field of defense during his term of office. As mandated by law. So that it can be implemented, the policy is described in the Minister of Defense Regulation Number: KEP/487/M/V/2021 Date: May 6, 2021, concerning the 2021 State Defense Policy, which contains the management of defense areas as one of its strategic objectives. Descriptive research approach using qualitative methods is the choice of researchers for this phenomenon with research subjects policymakers and policy implementers by understanding how the policy is to manage defense areas and how to manage defense area management strategies in order to realize decentralized defense logistics depots, in the concept of island defense. -big island in TNI-AL perspective. From the results of the analysis and discussion, it is found that the concept of defense of large islands has not accommodated the pattern of TNI-AL operations, especially in layered defense operations. there is still a need for improvement and further discussion related to the concept of defense of large islands as a base of defense as well as the last fortress of layered defense